The Effect of Catalyst in the Process of Nano-Silica Particle Formation as a Hydrophobic Material - Ikhwanul Muslim; Wulan Safrihatini; Witri Aini (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2017)
Nano Silica is known as a hydrophobic material used to coat the material that further modifies the surface properties of the material. In this study the process of making nano silica material is using sol-gel method. The sol gel process is defined as the process of forming an inorganic compound through chemical reaction in solution at a low temperature wherein the process a phase changes from the colloidal suspension (sol) to a continuous liquid phase (gel). The types of catalyst were studied. The result was then applied to cotton, polyamide and silk fabrics. Acid catalyst showed the greatest moisture reduction based on Moisture Content and Moisture Regain evaluation in cotton and polyamide fabrics, whereas base catalysts showed a significantly less moisture reduction on the three fabrics. The use of these types of catalyst will also affect the value of the tensile strength of each fiber. Tensile test results showed that the use of acid catalysts decreased the maximum tensile strength in cotton fabrics by 88.57%, compared to polyamide and silk fabrics and the use of base catalyst showed less significant decreased on tensile strength for all fabrics.